2003
DOI: 10.1094/pdis.2003.87.8.890
|View full text |Cite
|
Sign up to set email alerts
|

Toxoflavin Produced by Burkholderia glumae Causing Rice Grain Rot Is Responsible for Inducing Bacterial Wilt in Many Field Crops

Abstract: Severe wilt symptoms similar to bacterial wilt caused by Ralstonia solanacearum were observed in tomato, hot pepper, eggplant, potato, perilla, sesame, and sunflower in 2000 and 2001 in Korea. From diseased crops at 65 different locations, we obtained 106 isolates that produced green pigment on CPG medium; 36 were isolated from discolored rice panicles. The causal pathogen was identified as Burkholderia glumae based on its biochemical characteristics, fatty acid methyl ester analysis, and 16S rRNA gene sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
141
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(159 citation statements)
references
References 22 publications
1
141
0
8
Order By: Relevance
“…Although a eukaryotic host cell for Ralstonia sp. NT80 has yet to be identified, several species belonging to the genera Ralstonia and Burkholderia are known to infect plant cells (Cottyn et al, 1996;Jeong et al, 2003;Coenye et al, 2003). As described above, land plants use fatty alcohols, including stearyl alcohol, in the form of waxes (Buschhaus & Jetter, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although a eukaryotic host cell for Ralstonia sp. NT80 has yet to be identified, several species belonging to the genera Ralstonia and Burkholderia are known to infect plant cells (Cottyn et al, 1996;Jeong et al, 2003;Coenye et al, 2003). As described above, land plants use fatty alcohols, including stearyl alcohol, in the form of waxes (Buschhaus & Jetter, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…La técnica de Biolog es considerada como una herramienta muy útil y confiable en la identificación de aislamientos de B. glumae (Jeong et al, 2003;Yang, 2004;Nandakumar et al, 2009). Alternativamente se puede utilizar perfiles de ácidos grasos para realizar la identificación de la bacteria, obteniéndose muy buenos resultados con el sistema Sherlock Microbial (Jeong et al, 2003;Weinberg et al, 2007).…”
Section: Técnicas De Diagnósticounclassified
“…Bylund and colleagues (5) also recently demonstrated that ingested Burkholderia induced significant levels of necrosis in neutrophils from patients with CGD, suggesting yet another mechanism to explain the severe pathology seen with Burkholderia infection in this patient population. B. glumae, first described in Japan in 1976 (33), has been isolated in association with various plants including tomato, hot pepper, eggplant, potato, perilla, sesame, and sunflower (17). It is found epiphytically on rice leaves and in the rice rhizosphere (32) and is an important pathogen of rice, being implicated as a major cause of rice grain discoloration and seedling rot (9,10,14,33).…”
Section: Case Reportmentioning
confidence: 99%